Places not cases?Rethinking probation: the effects of nonprofit organizations on rearrest rates of probationers - Wo, James C. (Crime & delinquency, 2019)
Although scholars have theorized that nonprofit organizations (NPO) contribute to social control in communities, the relationship between NPO and rates of misconduct on the part of certain at-risk groups has received little empirical attention. The current study extends the literature by adopting a place-based approach to understanding differences in probationer misconduct that highlights the role of NPO in communities. Using longitudinal data from New York State counties, we analyze the linear and nonlinear influences that different NPO have on rearrest rates of probationers. Whereas most criminological theories suggest that NPO have a linear and salutary influence, we find evidence of a more nuanced process: NPO unexpectedly show evidence of exerting both salutary and deleterious influences on probationer outcomes.